The Venetian Qur'an : a Renaissance companion to Islam - Tommasino, Pier Mattia (University of Pennsylvania Press, 2018)
In The Venetian Qur'an, Pier Mattia Tommasino uncovers the author, origin, and lasting influence of the Alcorano di Macometto, a book that purported to be the first printed European vernacular translation of the Qur'an.